Evaluasi Pemahaman Standar Operasional Prosedur Tentang Premarital Skrining Pada Bidan Koordinator - Thalib, Kiki Uniatri; Rahmat, Rezqiqah Aulia; Pannyiwi, Rahmat; Jariyah, Ainun; Qudratullah, Fyzria; Vandika, Arnes Yuli (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Continuous professional development is the most important investment in human resources. Performance assessment and validity of performance professionalism can help develop the capabilities of health service providers. The purpose of PkM is to improve the understanding of standard operating procedures for premarital screening in midwives coordinators in service quality. The method used in PkM activities is to describe the characteristics of midwives coordinators (length of service, last education) in the work area of ​​the Health Center in Mamuju. The results of community service that the understanding of standard operating procedures for premarital, midwives coordinators have a good understanding of the response, so that understanding of standard operating procedures can later be the beginning of changes in midwives in providing education on premarital. The conclusion of this activity is that the majority of midwives coordinators have worked for > 10 years as many as 31 midwives (83.78%) and the last education of midwives is the most 17 midwives (45.95%) with the last education of diploma three and diploma four.